Presença de anticorpos anti-Neospora caninum e Toxoplasma gondii em cães com leishmaniose visceral da região de Araçatuba, São Paulo, Brasil - Gennari, Solange Maria; Cañón-Franco, William Alberto; Feitosa, Mary Marcondes [UNESP]; Ikeda, Fabiana Augusta [UNESP]; Lima, Valéria Marçal Felix de [UNESP]; Amaku, Marcos (My University, 2006)
Dogs that had positive and negative sera to Leishmania chagasi from the region of Araçatuba, São Paulo, Brazil, were evaluated for the presence of anti-Neospora caninum and anti-Toxoplasma gondii antibodies as potential co-infecting agents. Blood samples were collected from 204 dogs and out of them 98 were carriers of leishmaniosis. Sera were tested for the presence of anti-L. chagasi antibodies by ELISA, and anti-T. gondii and anti-N. caninum by an indirect fluorescent antibody test (IFAT). Age, gender, and association between the presences of anti-L. chagasi antibodies and seroprevalence to N. caninum and T. gondii were analyzed by chi-square test. Out of the 204 sera investigated, 36 (17.6%) were positive for N. caninum (IFAT=50) and 75 (36.8%) to T. gondii (IFAT=16) with titers that varied from 50 to 6400 for N. caninum, and from 16 to 16384 for T. gondii. The copresence of anti-L. chagasi, N. caninum and T. gondii antibodies was observed in 17 (8.3%) dogs. Antibodies to N. caninum were observed in four (3.8%) out of 106 dogs that were negative for L. chagasi, and in 32 (32.6%) out of the 98 dogs that were positive for L. chagasi. Anti-T. gondii antibodies were found in 40 (41.0%) and in 35 (33.0%) of the 98 positive dogs and in 106 negative dogs for L. chagasi, respectively. An association between the presence of antibodies against L. chagasi and a positive response to N. caninum (p<0.001) was observed. The gender and age of the dogs did not show an association between the presence of antibodies and any of the agents studied (p>0.05), with the exception of age and presence of anti-L. chagasi antibodies, in which only a slight association was observed (p=0.038). Within this interaction, a higher number of dogs, older than four years, were positive for this agent when compared to other age groups.
Presence of anti-Neospora caninum and Toxoplasma gondii antibodies in dogs with visceral leishmaniosis from the region of Araçatuba, São Paulo, Brazil
Keywords: Brazil; Dogs; Epidemiology; Leishmania chagasi; Neospora caninum; Toxoplasma gondii; Canis familiaris; Leishmania donovani chagasi